Distribution and abundance of some benthic fishes in the Abrolhos area (Brazil) - Paiva, Melquíades Pinto; Fonteles Filho, Antônio Adauto (Arquivos de Ciências do Mar, 2018)
The Abrolhos area is an important fishing zone for benthic fishes inhabitant of rocky substrates, among which stand out the followingspecies,indecreasingorderofimportance:grouper=Epinephelusguaza(Linnaeus, 1758),blackgrouper=Mycteroperca bonaci (Poey, 1860), and yellowtail snapper = Ocyurus chrysurus (Bloch, 1791). As a whole, these species made up 73.3% of a mean annual production of 696,562kg (1986-1989). These are the dominant fishes in the biocenosis, to the order of 31.7% (grouper), 25.5% (black grouper), and 16.1% (yellowtail snapper) of its biomass. Their higher yields were taken in the third quarter and the lower ones in the fourth quarter. The overall index of abundance was 2.03kg/hook-day, with individual values of 0.64kg/hook-day for the grouper, 0.52kg/hook-day for the black grouper, and 0.33kg/hook-day for the yellowtail snapper. Fishing effort is highly concentrated, 88.3% being applied upon a subarea equivalent to 21.2% of the overall fishing area, catches therein account for 87.1% of total production. In relation to the dominant species, in this subarea were made 83.7% of the grouper catches, 87.7% of the black grouper catches, and 92.1% of the yellowtail catches. Grouper and black grouper are found in the whole breadth of the continental shelf, but yellowtail snapper are distributed up to 80 meter-deep grounds. Fishing production is concentrated in the depth range of 31-60m in the following proportions for the three species: 90.8%, 89.9%, and 92.7%, respectively.